1997
DOI: 10.1099/00221287-143-1-23
|View full text |Cite
|
Sign up to set email alerts
|

Colonial Opacity Variations among the Choleragenic Vibrios

Abstract: Cultures of Vibrio cholerae 01, biotype El Tor, from the current epidemic of cholera in the Western Hemisphere, and of the new V. cholerae serogroup 0139, from the current outbreak in India and Bangladesh, revealed marked colonial heterogeneity when received by the authors. By comparison with reference colony types, using a stereoscope and transmitted oblique illumination, colonies of approximately 10 different degrees of opacity could be distinguished. In contrast, strains freshly isolated from patients and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…Interestingly, the translucent ompU mutant (lane 7) contains predominately the medium molecular mass O-antigen and very little of the lipid A core. This LPS profile is similar to a translucent variant of a wild-type V. cholerae strain (Finkelstein et al, 1997). These data suggest that changes in the OMP content can alter the amount and length of the smooth LPS in the outer leaflet of the cell.…”
Section: Lps Profilessupporting
confidence: 53%
“…Interestingly, the translucent ompU mutant (lane 7) contains predominately the medium molecular mass O-antigen and very little of the lipid A core. This LPS profile is similar to a translucent variant of a wild-type V. cholerae strain (Finkelstein et al, 1997). These data suggest that changes in the OMP content can alter the amount and length of the smooth LPS in the outer leaflet of the cell.…”
Section: Lps Profilessupporting
confidence: 53%
“…Other cultures were from ATCC, J. Johnson (VA Medical Center, Baltimore, MD, USA), J. Mekalanos (Harvard Medical School, Boston, MA, USA), G. B. Nair (National Institute of Cholera and Enteric Diseases, Calcutta, India), Y. Takeda (International Medical Center of Japan, Tokyo, Japan), R. Taylor (Dartmouth Medical School, Hanover, NH, USA), K. Wachsmuth (Centers for Disease Control and Prevention, Atlanta, GA, USA) and our laboratory collection ( University of Missouri, MO, USA). Colony morphology and opacity were evaluated as previously described (Finkelstein et al, 1997). T o evaluate the potential role of TcpA as a receptor (Waldor & Mekalanos, 1996) for phage 493, ToxR-mutants of A 527-493 were made according to a modification of a previously described technique (Waldor & Mekalanos, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…Growing cells were picked from the centre of plaques and streaked for single colonies. Stereoscopic examination of these colonies using transmitted oblique illumination (Finkelstein et al, 1997) revealed that marked alteration in colonial morphology occurred as a result of infection with phage 493 (Fig. La, b).…”
Section: Infection By Choleraphagementioning
confidence: 99%
“…To our knowledge, this is the first report of phase-variable expression of O antigen in S. typhimurium. There is precedence for phase-variable expression of LPS in other bacterial genera, including Vibrio (14), Neisseria (2,43,48), Haemophilus (42,53,54), and Chlamydia (30).…”
Section: Discussionmentioning
confidence: 99%